Correlation of Physical Spaces, Mental Health and Work Performance in Lockdowns- the Case of Saudi Arabia (American Journal of Interdisciplinary Research and Innovation, 2023)
In order to determine the influence of the COVID-19 pandemic on the mental health of workers’ cognitive performance, as well as on work engagement and work environment, we anticipated that there would be a correlation between the variables. The study included 600 participants, of whom 597 responded, resulting in data collection from 597 participants. The participants’ approval was required before any demographic data could be obtained. The study was carried out during the first pandemic wave, which brought about an immediate lockdown and compelled the majority of the firm to switch to having their employees work from home. The results of the data suggested that there was only a very little correlation between the variables, however the outcomes of the research revealed that there was a definite relationship. It is not notable, in this research’s outcomes that leaning on social resources may help decrease COVID-19 anxiety. This discovery comes at a time when the favorable theoretical effect of work crafts continues to rise.